Internal capital markets and return predictability in complex ownership firms - GONZALEZ, Angelica (Institutional Knowledge at Singapore Management University, 2021)
Using global cross-ownership data, we find return predictability for four possible cases in ownership-linked firms (OLFs): subsidiary−parent, parent−subsidiary, subsidiary−subsidiary, and parent−parent. A long/short portfolio strategy sorted by the lagged monthly returns of OLFs yields the monthly Fama-French six-factor alpha of 79−113 bps. These results, which are observed only after the establishment of ownership links, are not subsumed by industry or cross-country momentums or by alternative inter-firm relations, including customer−supplier links, strategic alliances, common boards, and shared analyst coverage. The OLF return predictability is best explained by active internal capital markets—a mechanism unique to firms with a complex ownership network.